(untitled) (Ameghiniana, 2014)
This is a systematic study of the palynological assemblages recorded in the upper part of the La Veteada Formation (upper La Veteada Association), which constitutes the section of the type locality, La Rioja Province, Argentina. In this contribution, 72 species of striate (monosaccate and bisaccate), plicates and colpate pollen grains are presented. Four new species are described: Meristocorpus veteadensis sp. nov., Lueckisporites biformis sp. nov., Lunatisporites lenticularis sp. nov., and Marsupipollenites costatus sp. nov. and, a new combination, i.e., Striatopodocarpites gopadensis (Bharadwaj and Srivastava) comb. nov is proposed. This palynoflora has a marked dominance of striate pollen grains which have great species diversity of Striatopodocarpites (with 11 species)-Protohaploxypinus (9 species)-Lueckisporites (9 species)-Lunatisporites (8 species) complex, showing scarse participation of the genera Vittatina, Weylandites, Marsupipollenites, Corisaccites, Staurosaccites and Pakhapites, as well as pollen grains referred to Cordaitales (Potonieisporites, Cannanoropollis, Caheniasaccites, Plicatipollenites, Barakarites). It shares taxa recorded in the LW (Argentina), Vc-Lv (Brazil) and IS-AC (Uruguay) biozones. Tables include full taxonomic composition of the microflora of the La Veteada Formation at its type locality, the palynostratigraphic correlation of the Neopaleozoic strata of central Argentina, southern Brazil and Uruguay, and the global previous stratigraphic records of the species recorded and discussed herein. The palynoflora of the upper La Veteada Formation is referred to the Late Permian (Lopingian) based on the stratigraphic range of all the recognized species. Consequently, it is considered the youngest Permian palynoflora recorded hitherto in Argentina and South America.